DETEKSI KOI HARPES VIRUS (KHV) PADA IKAN MAS KOI (Cyprinus carpio L) DENGAN MENGGUNAKAN METODE APLIKASI Polym erase Chain Reaction(PCR) - Masri, Mashuri (Fakultas Sains dan Teknologi UIN ALauddin, 2013)
This thesis discusses the detection of koi harpes virus (KHV) in koi carp (Cyprinus carpio L) Application Method Using the Polymerase Chain Reaction (PCR). The purpose of this study is to determine the level of virus attacks causing harpesviridae group KHV Koi carp (Cyprinus carpio L.) using PCR applications in the Central Fish Karantian Hasanuddin Makassar. The research method used is descriptive with pictures PCR of Polaroid photographs. The results obtained with the results of attacks lightly infected 290 bp, the attack was infected with the results of 290 bp and 440 bp, with the result of severeinfection attack 290 bp 440 bp and 630 bp.Keywords: Koi Harpes Virus (KHV), Koi carp (Cyprinus carpio L) and PCR.